1998
DOI: 10.1046/j.1365-8711.1998.01480.x
|View full text |Cite
|
Sign up to set email alerts
|

FRII radio galaxies with z < 0.3 - I. Properties of jets, cores and hotspots

Abstract: In previous papers we have discussed high-resolution observations of a large sample of powerful radio galaxies with z < 0.3. Jets are detected in up to 80 per cent of the sample, and radio cores in nearly all the objects; in addition, we are able to resolve the hotspots in most sources. In this paper we present measurements of the radio properties of these components.The prominences of the jets detected do not appear to be a function of radio luminosity, providing the clearest evidence yet that the reported lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 42 publications
(48 reference statements)
12
120
1
Order By: Relevance
“…In line with trends reported by Hardcastle et al (1998), some BLRGs such as superluminal, cool 3C 111 and optically variable, hot 3C 390.3 are undoubtedly low-power QSRs, observed at small inclination angles. Cohen et al (1999) and Dennett-Thorpe et al (2000) however point out that other BLRGs must be identified with critically inclined QSRs, i.e., radio sources observed close to or through their torus boundary.…”
Section: Discussionsupporting
confidence: 87%
“…In line with trends reported by Hardcastle et al (1998), some BLRGs such as superluminal, cool 3C 111 and optically variable, hot 3C 390.3 are undoubtedly low-power QSRs, observed at small inclination angles. Cohen et al (1999) and Dennett-Thorpe et al (2000) however point out that other BLRGs must be identified with critically inclined QSRs, i.e., radio sources observed close to or through their torus boundary.…”
Section: Discussionsupporting
confidence: 87%
“…On kiloparsec scales, 3C 98 shows a double-lobe FRII radio structure which spans 216 arcsec at 8.35 GHz, with a radio jet that crosses the northern lobe and terminates in a bright hotspot. There is little evidence of a southern jet, but a twin hotspot in the southern lobe is present (Hardcastle et al 1998). The core of this symmetric FRII radio galaxy is pointlike in our VLBI image, with the total flux density ∼2.2 mJy.…”
Section: +10 -(3c 98) -mentioning
confidence: 72%
“…Because of the optical identification this source will not be considered in the following discussion. 0802+24 (3C 192) -On large scale, this radio source shows an "X" symmetric double-lobe structure which extends ∼200 arcsec at 8.35 GHz, showing bright hotspots at the end of the lobes (Baum et al 1988;Hardcastle et al 1998).…”
Section: +10 -(3c 98) -mentioning
confidence: 95%
“…High resolution radio images for all but one object, 3C 403.1, were available. All relevant optical spectroscopic classifications are extracted from Jackson & Rawlings (1997), Hardcastle et al (1998Hardcastle et al ( , 1999, and Morganti et al (1997). We note that BLRG 3C 120 differs from the rest of the selected BLRG subsample, since it is strongly core-dominated and has a FR-I morphology.…”
Section: Sample Selectionmentioning
confidence: 99%